Retrospective Evaluation of the Severity of Creatine Kinase Elevation in Canine and Feline Trauma Patients as a Predictor of Morbidity and Mortality - Hurst O; Mastrocco A; Prittie J; Hadala A; Weltman JG (Veterinary Medicine: Research and Reports)
Owen Hurst,1 Alicia Mastrocco,1 Jennifer Prittie,1 Ashley Hadala,2 Joel Green Weltman1 1Emergency and Critical Care, Schwarzman Animal Medical Center, New York, NY, USA; 2Soft Tissue and Orthopedic Surgery, Schwarzman Animal Medical Center, New York, NY, USACorrespondence: Owen Hurst, Schwarzman Animal Medical Center, 510 East 62nd Street, New York, NY, 10016, USA, Email owen.hurst@amcny.orgPurpose: To assess if severity of creatine kinase (CK) elevation in veterinary trauma patients is associated with overall patient morbidity (need for blood products or surgery, prolonged hospitalization) and mortality.Patients and Methods: Five hundred and eight-three dogs and cats experiencing trauma with an admission CK > 1000 U/L over a 15-year period were included in this study. The population was further stratified based on severity of CK elevation to include 161 dogs and 133 cats with admission CK > 5000 U/L, and 211 dogs and 78 cats with admission CK between 1000 and 5000 U/L. These groups were then compared for likelihood of trauma-associated morbidity, including increased need for blood products, surgical intervention, and/or hospitalization time. The likelihood of mortality was also compared between groups.Results: The need for packed red blood cell transfusion and length of hospitalization were significantly increased in traumatized dogs and cats with CK > 5000 U/L. Higher CK was not associated with increased surgical needs. Dogs with CK > 5000 U/L had significantly higher mortality rate compared to < 5000 U/L.Conclusion: A higher degree of CK elevation is associated with need for blood products and prolonged hospitalization in dogs and cats and higher mortality in dogs. Evaluation of the severity of CK levels on presentation, and serial evaluation of the same, may aid in the assessment of trauma severity and prognosis in veterinary trauma patients.Keywords: blood transfusion, muscle injury